E EDUKASI PENINGKATAN KUALITAS HIDUP DAN PEMBEKALAN PERENCANAAN KEUANGAN UNTUK MASYARAKAT DESA LABUAN PANDEGLANG - BANTEN - Eri Bukhari; Fadhli Nursal (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2022)
One of the ways to improve the quality of life in the household is to be supported by good household financial management, and for that it is necessary to carry out household financial planning as early as possible. The purpose of this Community Service is to educate the improvement of the quality of life by providing financial planning to the people of Labuan Village, Pandeglang - Banten. The reason for the importance of this activity is that the majority of the villagers work as traders and their income is uncertain, coupled with their relatively low level of formal education. This condition, if not equipped with good financial literacy, has the potential to result in poor financial management for their household. The method implemented is to make observations and counseling, namely by systematically observing and recording the symptoms/phenomena being investigated, because it turns out that the surrounding community has a low quality of life and lacks an understanding of how to manage finances properly so that the financial goals they expect are achieved. The results of this financial planning briefing are expected that the people of Labuan Village will be able to practice how to manage household finances to be more organized, planned and wise for the sake of economic resilience, resulting in a better quality of life.Keywords: Education, Finance, Economic Resilience